Características estruturais da parede das artérias renal e femoral de coelho (Oryctolagus cuniculus) - Viegas, Katia Aparecida da Silva; Marcos Orsi, Antonio [UNESP]; Simões, Karina; Fantin Domeniconi, Raquel; Marçal Natali, Maria Raquel (My University, 2004)
In the renal and femoral arteries of rabbit was verified that both vessels had walls structured by myostromal components, despite of their different distributive of blood, being the renal artery a visceral blood vessel and the femoral artery a parietal vessel. This wall pattern in these vessels concerned to presence of connective stromal elements (collagen and elastic fibres and lamellae) and smooth muscle cells coexisting with some equilibrium in the wall structure of the renal and femoral arteries, mainly in the medial layer architecture. An intimal folding pattern was verified around the vascular lumen, possibly related to capacitance of the both arteries regarding to variability of pressure levels in cardiac cycle. Furthermore, myostromal relations of connective elements and smooth muscle cells verified in the medial layer and the network formed by connective elements in the adventitial layer of these arteries contributed to maintenance of wall viscoelasticity properties of the vessels.
Structural features of the renal and femoral arteries wall in rabbit (Oryctolagus cuniculus)
Keywords: Femoral artery; Histoarchitecture; Rabbit; Renal artery; Vascular wall; collagen; artery wall; blood flow; elastic fiber; femoral artery; lamellar body; nonhuman; rabbit; renal artery; smooth muscle fiber; structure analysis; viscoelasticity; Oryctolagus cuniculus